Jurisprudencia constitucional sobre libertades públicas 2012: Casos y reglas - Álvarez Álvarez, Leonardo; García Luengo, Javier; Álvarez Fernández, Mónica; Fernández Villazón, Luis Antonio; Ceínos Suárez, Ángeles; Palacios González, María Dolores; García, Luz María (Revista Jurídica de Asturias, 2013)
Sin resumen